Training of Breast Examination (Best Self-Examination) in the Order of Improving the Independence of Adolescent Care of Reproductive Health in the Pandemicovid-19 Time at Senior High School 1 Telaga - Ani Retni; Harismayanti; Siti Nur Khaliza Djauhari; Sartika Olii; Muhlis Tahir (Journal of Universal Community Empowerment Provision, 2021)
Producer health is a problem that needs special attention among teenagers. Public awareness and knowledge of cancer including risk factors, prevention efforts, symptoms that arise, and early detection of cancer is still lacking so it is necessary to increase knowledge for young women. 1 Lake in the context of increasing the independence of adolescents who care about reproductive health during the covid-19 pandemic. From the results achieved with this activity, the school is very supportive and gives thanks to the Muhammadiyah University of Gorontalo in carrying out the activities that have been carried out. The conclusion of this community service is that counseling can increase the knowledge of participants in breast self-examination (BSE) training